Integrative analysis of metabolites and microbial diversity revealed metabolic mechanism of coarse feeding tolerance in Songliao Black sows during gestation - Zhao, Jinbo; Zhao, Wenjiang; Dong, Jiaqiang; Zhang, Hong; Yang, Kun; Gao, Shengyue; Feng, Wanyu; Song, Yan; Qi, Meiyu; He, Xinmiao (Frontiers in Microbiology, 2024)
Dietary fiber is a key nutritional regulatory factor that has been studied intensively for its role in improving reproduction in sows during gestation. However, the metabolic mechanism underlying the effect of interactions between metabolites and gut microbes on coarse feeding tolerance in indigenous sows remains to be elucidated. Therefore, the present study aimed to investigate the effects of dietary supplementation with alfalfa at different content ratios on reproductive performance of pregant Songliao Blacks sows. Forty Songliao Black sows at 30 days of gestation were allocated to four treatments, which received the following diets: 1) a corn-soybean meal basal diet with no alfalfa meal (CON group), 2) a corn-soybean meal basal diet + 10% alfalfa meal (Treatment 1 group), 3) a cornsoybean meal basal diet + 20% alfalfa meal (Treatment 2 group), and 4) a corn-soybean meal basal diet + 30% alfalfa meal (Treatment 3 group). The results revealed that meals with 10% and 20% alfalfa had a beneficial effect on sows in terms of improving the reproductive performance of these sows. Bacterial 16S rDNA sequencing of the fecal samples revealed that the 10% alfalfa meal group had a higher αdiversity and higher abundance of probiotics. Bacteroidetes, Firmicutes, Proteobacteria, and Actinobacteria were revealed as the most abundant groups at the phylum level and Lactobacillus, Prevotella, Ruminococcus, Streptococcus, and Clostridium were the most abundant at the genus level in the sows fed with diets containing higher fiber levels. A total of 239 differential metabolites were identified in the sows fed with alfalfa meals. These metabolites were enriched mainly in the cAMP signaling pathway, biosynthesis of amino acids, and steroid biosynthesis. Pearson correlation analysis revealed significant positive correlations between Blautia and Daizein, Fibrobacter and 5-alpha-Cholestanone, Sphaerochaeta, Sutterella, and Metaraminol. Negative correlations were revealed between Sphaerochaeta and Erucic acid, Prevotellaceae and Harmaline, and Streptococcus and 5alpha-Cholestanone. Collectively, these findings provide novel insights for the application of dietary fiber in sow diets.